Hybrid and pristine polyalkylthiophene Langmuir-Schaefer films: Relationships of electrical impedance spectroscopy measurements, barrier properties and polymer nanostructure - de Lima Citolino, Lucas Vinicius [UNESP]; Assunção da Silva, Edilene [UNESP]; de Almeida Olivati, Clarissa [UNESP] (Elsevier, 2019)
Molecular organization in solid state plays a central role on organic devices performance. In this sense, a thorough investigation of thin films with application in organic electronics is imperative. This work addressed the fabrication and the morphological, optical and electrical characterization of Langmuir-Schaefer (LS) films of poly(3-hexylthiophene) (P3HT), pristine and mixed with stearic acid (SA), and their use as the active layer in organic Schottky diodes. The floating materials isotherms showed the SA molecules acting as a stabilizer for the P3HT in the Langmuir trough. Moreover, deposited P3HT:SA films present significant morphological changes, an improvement of the films overall structural ordering and a more effective charge transport within the active layer through electrical outcome. The alternating current measurements along with theoretical fitting, using equivalent electrical circuits, provided a good alternative to investigate the interfacial effects of the P3HT and P3HT:SA films deposited onto Al and Au electrodes.
Keywords: Electrical impedance spectroscopy; Langmuir-Schaefer; Polythiophene; Structure-property relations; Thin films